2003
DOI: 10.1063/1.1601308
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling microscopy and spectroscopy of multiwalled boron nitride nanotubes

Abstract: Atomic resolution images of multiwalled boron nitride nanotubes have been obtained using scanning tunneling microscopy operating at tunneling currents below 20 pA and biases of approximately −2.5 V. Lattice images acquired with negative sample biases exhibit trigonal symmetry that is interpreted as resulting from nitrogen states. Tunneling spectroscopy confirms band gaps between 4.5 eV and 4.8 eV for tube diameters above 5 nm. Tunneling barrier height measurements made using standard current–distance analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 15 publications
3
44
0
Order By: Relevance
“…Band gaps of 4.5 to 4.8 eV for nanotube diameters >5 nm were measured [10]. We are not sure how to reconcile those gaps in the tunneling densities of states with the current quasiparticle band gap energies from theories of single-walled…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Band gaps of 4.5 to 4.8 eV for nanotube diameters >5 nm were measured [10]. We are not sure how to reconcile those gaps in the tunneling densities of states with the current quasiparticle band gap energies from theories of single-walled…”
Section: Methodsmentioning
confidence: 98%
“…Multi-walled BN nanotubes were grown by an arc generator method [10] and were characterized by tunneling microscopy and tunneling spectroscopy on single nanotubes. Band gaps of 4.5 to 4.8 eV for nanotube diameters >5 nm were measured [10].…”
Section: Methodsmentioning
confidence: 99%
“…The number of discovered TiO 2 polymorphs is seven, 2 although rutile and anatase undoubtedly prevail because of their higher stability as compared to other titania phases. Nanotubes (NTs) of different morphology from these substances were systematically synthesized during the last 10-15 years and carefully studied as prospective technological materials, both for BN [3][4][5][6][7] and TiO 2 . [8][9][10][11] One recently discovered nanotube application was doping of TiO 2 NTs by boron and nitrogen atoms 12 gradually varied their band gaps.…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up computational study showed that to the contrary of CNTs, BNNTs should always be semiconducting and their band gaps should not depend on their chirality and diameter [153]. Soon after, the synthesis of BNNTs was demonstrated [154], and a series of measurements on single and multi-wall nanotubes confirmed the absence of correlations between chirality, diameter and band gaps [155][156][157]. The reported experimental (from multi-walls up to single walls nanotubes) band gap values from 4.5 to 5.8 eV are in good agreement with the computed GW value of 5.5 eV.…”
Section: Electronic Materialsmentioning
confidence: 99%